KOMUNIKASI KELUARGA DALAM MENGHADAPI FENOMENA CHILDFREE PADA GENERASI MILENIAL - Dena Anggita Khalis (2024)
The terms of childfree or someone's desire not to have children is currently developing in Indonesia, since a famous YouTuber named Gita Savitri stated her choice to be childfree and responded to the pros and cons from the public. Researchers consider it necessary to examine this phenomenon from a family communication perspective because the decision to have or not have children is closely related to the concept of family. This research aims to find out how family communication experiences in dealing with the childfree phenomenon in the millennial generation and how this concept is interpreted in the millennial generation through the theory of symbolic interactionism put forward by George Herbert Mead. This type of research is descriptive-qualitative using phenomenological methods. Research shows that the millennial generation uses symbols of choice and lifestyle as meaning in interactions with the childfree phenomenon. The findings also show that the millennial generation's family communication experiences regarding childfree also shape how they respond and interpret this issue. Keywords: family communication, childfree phenomenon, phenomenology studies, millennial generation, symbolic interactionism.